2017
DOI: 10.1590/0034-7167-2016-0344
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities of care for serodiscordant couples for HIV who got pregnant

Abstract: Objective: Understanding the meaning of pregnancy for heterosexual couples facing serodiscordant situation for HIV, aiming at construction of care possibilities based on subjectivity. Method: Phenomenological research, theoretical-philosophical-methodological framework by Martin Heidegger. Research was conducted in a University Hospital in the countryside of Southern Brazil, from September 2013 to May 2014 through a phenomenological interview, with participation of eleven couples. Results: For the couples, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
1
0
3
Order By: Relevance
“…Still, in volume 05, rights were addressed: the desire to have children, family planning, and the fundamental rights for ILWHA. And although HIV brings fears and apparent limitations to ILWHA ( 24 ) , the desire for plans related to maintaining or building affective-sexual and family relationships, as identified in this study, is legitimate and can be found in others studies with different populations of ILWHA, such as men who have sex with men(24), pregnant woman ( 25 ) and serodifferent couples ( 26 ) .…”
Section: Discussionmentioning
confidence: 71%
“…Still, in volume 05, rights were addressed: the desire to have children, family planning, and the fundamental rights for ILWHA. And although HIV brings fears and apparent limitations to ILWHA ( 24 ) , the desire for plans related to maintaining or building affective-sexual and family relationships, as identified in this study, is legitimate and can be found in others studies with different populations of ILWHA, such as men who have sex with men(24), pregnant woman ( 25 ) and serodifferent couples ( 26 ) .…”
Section: Discussionmentioning
confidence: 71%
“…El enfermero presenta amplias oportunidades de ofrecer cuidados a las alianzas serodiscordantes al VIH, entre los mencionados en los estudios está la consulta de enfermería, donde el enfermero realiza de forma ampliada la evaluación de alianzas serodiscordantes que van desde los aspectos clínicos a las necesidades psicoemocionales, afectivas, sexuales, sociales, así como la recepción de sus subjetividades (4,11,13,25) .…”
Section: Discussionunclassified
“…A construção de espaços dialógicos nos momentos de atenção à saúde (4) oportuniza a narrativa da mulher sobre suas vivências (8) . Por meio da escuta sensível, a enfermagem pode conhecer a realidade vivenciada pela mulher, seus sentimentos e desejos atrelados à maternidade (1) .…”
Section: As Limitações Da Mãe Soropositiva Para O Hivunclassified
“…Esse diagnóstico encontra-se imbricado com diversos sentimentos (1) , podendo influenciar na escolha pela maternidade (2) . Compreende-se que a soropositividade para o HIV pode não dissipar o desejo da maternidade (1) , sendo a gestação algo desejado e planejado pela mulher (3) ou pelo casal (4) .…”
Section: Introductionunclassified
See 1 more Smart Citation